Qualitative data analysis key approaches - Stevens, Peter A.J (SAGE, 2023)
With numerous approaches to choose from, knowing where to start when doing qualitative data analysis (QDA) can be a challenge. This book gives you direction with an accessible and thorough introduction to nine different approaches to QDA, written by a multi-disciplinary team with years of experience. With a clear focus on the 'how to' of QDA, each chapter includes: Step-by-step descriptions of how to apply each approach in your research - Activities to help you practise your skills - Annotated reading lists so you can dig deeper into key topics - Case studies from a range of disciplines so you can see how each approach works in practice. The perfect companion on your journey through QDA, the book also offers a comprehensive introduction to the use of NVivo QDA software, helping both new and experienced researchers get to grips with the essentials"--